FACTORS INFLUENCING THE FORMATION OF BURNOUT SYNDROME IN PATIENTS WITH WORKPLACE HYPERTENSION - Yu. P. Zinchenko; E. I. Pervichko; O. D. Ostroumova (Рациональная фармакотерапия в кардиологии)
Aim. To study the relationship of psychological factors (perfectionism and mechanisms of psychological defense), with the presence and qualitative characteristics of the "burnout syndrome" in patients with "workplace hypertension" (WPH), in comparison with other patients with essential hypertension (HT) and healthy individuals. Material and methods. 170 untreated patients with stage II HT (mean age 46.7±4.1 years) were examined. 85 patients with WPH were included into group 1 (46 men; mean age 44.7±4.3 years) and 85 patients without WPH – into group 2 (42 men; mean age 47.4±4.5 years). The control group consisted of 82 healthy individuals (45 men; mean age 44.9±3.1 years). The Russian version of Maslach Burnout Inventory (MBI), the Multidimensional scale of perfectionism by Hewitt and Flett (MPS), The Life Style Index (LSI) were used for “burnout syndrome” diagnose. Results. The relationship between perfectionism and "burnout" was found in all studied groups. The factor "socially prescribed perfectionism" was most associated with the "burnout" parameters in both groups of HT patients. In the WPH-group this relationship was more pronounced. The structure of perfectionism in WPH-patients is the most disharmonious in comparison with patients of the group 2 and healthy persons. The "socially prescribed perfectionism" was significantly more prevalent (76.6±3.9) compared with other indicators (62.1±4.3 and 61.5±3.6 for perfectionism oriented to others and to themselves, respectively). In the structure of the protective processes in HT patients of both groups with the maximal degree of excess of the values of healthy individuals two most archaic mechanisms [projection (69.1% and 40.8%) and negation (51.8% and 40.9%) in groups I and II, respectively] as well as one of the most mature protective processes (intellectualization - 53% and 47.9%, respectively) were revealed. Taken together, this shows a general "tension" of the system of protective processes. Statistically significant correlations between the high representation of the protective processes "negation" and "projection" with high values of the score according to MBI scales were found. Conclusion. Perfectionism and the "tension" of the mechanisms of psychological defense can be considered as the most important personal characteristics predisposing to the development of "burnout syndrome" in WPH-patients.